A Study to Assess the Effectiveness of Lukewarm Water Footbath Therapy on Quality of Sleep among Elderly People Staying in Nadiad - Jasmin Prakashbhai Patel; Bhoomi Bhoopendrabhai Patel; Shruti Bharatbhai Patel; Pavitra Sanjaykumar Prajapati; Janki Kamleshbhai Patel; Bhavisha Rameshbhai Sonara; Nickson Das (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Sleep is necessary for human being regardless of age. Specifically elderly people havecomplaints in sleep disturbances which if treated can improve quality to sleep.Aim: To identity the sleep quality among elderly people and to evaluate effectiveness of lukewarm waterfootbath therapy.Materials and Methods: An interventional study was conducted among 40 old age people staying in selectedold age home, Nadiad. The purpose of the study was to improve the quality of sleep amongst elderly. Thesamples were selected by non-probability convenient sampling technique. The tool used for data collectionwas Pittsburgh sleep quality index which is a self rated questionnaire. Lukewarm water foot bath therapywas used as an intervention after taking consent from the samples. Pre-test was conducted from samples byusing Pittsburgh sleep quality index followed by which researcher has given intervention (lukewarm waterfoot bath therapy) for 10 days consecutively before sleep at same time for 20 minutes. Later on, post-testwas conducted after 1 week by using Pittsburgh sleep quality index. Descriptive and inferential statisticswas used to analyze the data obtain was tabulated analyzed and interpreted in terms of objective of the study.Results: The demographic data related to age 12(27.9%) belonged to 71-75 years, gender 23(53.5%) werefemales and 17 (39.5%) were males, education the majority of the people 23 (53.5%) was from secondaryeducation, the source of income 16(37.2%) were having pension, social status 25(58.1%) was from middleclass, medications 23(53.5%) were taking and 17(39.5%) were not taking, factors affecting sleep 20(46.5%)were having anxiety, activity 15(34.9%) was doing recreational activity, night hours of sleep 16(37.2%)was having 6-7 hours, hours of sleep in day time 16(37.2%) was having 2-2.5 hours, habit 24(55.8%) washaving alcohol habit. Researcher applied Mann-Whitney test for comparison between pre-test and post-test.Calculated Mann-Whitney pre-test values were 2.5 and post-test values were 4.29 which prove there is asignificant effectiveness of lukewarm water footbath therapy on quality of sleep.Conclusion: It conclude that assessment of sleep quality after Lukewarm water footbath therapy shows thatthe lukewarm water footbath therapy is helpful for improving the sleep quality among the elderly.